Enhanced photoelectrochemical properties of visible light-responsive TiO2 photoanode for separate-type Pt-free photofuel cells by Rh3+ addition - Toyao, Takashi; Iyatani, Kazushi; Horiuchi, Yu; Moriyasu, Madoka; Cho, So-Hye; Takeuchi, Masato; Matsuoka, Masaya; Anpo, Masakazu (SPRINGER, 2013)
Visible light-responsive TiO2 (Vis-TiO2) electrode has been applied for the Pt-free separate-type photofuel cell (SPFC) where two different electrolytes containing various biomass derivatives and a I-3 (-)/I- redox solution were employed for the anode and cathode sides, respectively. This new SPFC exhibits good photoelectrochemical performance under simulated solar-light irradiation. It was found that the Rh3+ loading on Vis-TiO2 electrode enhanced the photoelectrochemical performance of the SPFC through the increase in the visible light absorption as well as the increase in the electron conductivity of Vis-TiO2 electrode.
Keywords: PHOTOCATALYTIC DEGRADATION; TITANIUM(IV) OXIDE; WATER; IRRADIATION; 2-PROPANOL; HYDROGENATION; SELECTIVITY